A travel cost analysis of elk-viewing opportunity generated from an elk reintroduction project in Tennessee. Issue 1 (2nd January 2022) - Chapagain, Binod P.; Poudyal, Neelam C.; Watkins, Cristina
ABSTRACT: Long-term success of wildlife restoration programs depends on their potential to bring economic benefits to stakeholders. Because of the non-market nature of some benefits (e.g., wildlife viewing), however, demonstrating the economic value of such programs is often challenging. By employing a travel cost model of elk-viewing trips among households around the North Cumberland Wildlife Management Area, Tennessee, this study estimated the net economic benefit of elk-viewing opportunities generated from an elk reintroduction program. Depending on the assumptions about visitors' opportunity cost of time, the net economic benefit of elk viewing was estimated to range from $21/trip to $53/trip. When aggregated across the population, the total economic value of the elk-viewing opportunity generated from this restoration program was estimated to be as high as $6.95 million. Results from this study will be useful in characterizing the economic benefits of elk viewing and providing economic justification for restoration programs.